Global impact of dietary risks on cancers: burdens across regions from 1990 to 2021 and the projection to 2035 - Xiangrong Liu; Xiangrong Liu; Xinsheng Zhang; Yulu Wei; Zhimeng Yu; Lu Liu; Xin Qin; Yinghua Liu (Frontiers in Nutrition)
BackgroundThe burden of cancer has been progressively increasing, with diet playing a key role in its development and progression. Previous studies on diet-related cancer burden mainly focused on individual factors or single cancer types. Therefore, this study aimed to analyze global trends in deaths and disability-adjusted life years (DALYs) associated with diet-related cancers from 1990 to 2021, predicting the burden up to 2035.MethodsUsing bibliometric analysis and Global Burden of Disease (GBD) 2021 data, it examined mortality and DALY rates stratified by age, sex, cancer type, and region. Decomposition analysis assessed contributions of population growth, aging, and epidemiological transitions, while health inequalities were evaluated using inequality indices. Frontier analysis quantified gaps between current and minimum achievable burdens. Future trends for multiple tumors were projected using Bayesian Age-Period-Cohort (BAPC) modeling.ResultsThe age-standardized death rate (ASDR) for diet-related cancers declined from 12.24 (95% UI: 3.32 to 22.78) per 100,000 in 1990 to 7.90 (95% UI: 2.45 to 13.85) in 2021, and the age-standardized DALYs rate decreased from 302.48 (95% UI: 80.53 to 565.63) to 189.62 (95% UI: 57.13 to 335.37) per 100,000. In 2021, the highest ASDR were recorded in Central Europe, and the largest age-standardized DALYs rate were documented in Southern Sub-Saharan Africa. The greatest disease burden was identified in high-middle sociodemographic index (SDI) regions. Colon and rectum cancers were most prominent, with high red meat intake as the leading dietary risk. We also found that a higher disease burden was observed in males compared to females, and the burden increased progressively with age. Decomposition analysis revealed population growth as the main driver of increasing burdens, partly offset by epidemiological changes. Health inequality driven by economic factors has decreased. BAPC modeling predicted a continued decline in the future burden of multiple cancers, except for breast cancer.ConclusionWhile the burden of diet-related cancers is declining, challenges remain, particularly in older populations and higher SDI regions. Persistent health inequalities affect esophageal and stomach cancers. These findings can guide targeted strategies for prevention and control.